Francisella-like endosymbiont and Rickettsia aeschlimannii co-infection in a Hyalomma marginatum tick - Carvalho, C.L. (2017)
Abstract publicado em: E-SOVE 2016 the 20th Conference, Book of Abstract, 3th-7th October 2016, Lisbon - Portugal. doi:10.3920/978-90-8686-837-7, p. 159